Destruction of low-temperature insulation under the condition of periodic duty; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Polovnikov V. Yu. Vyacheslav Yurievich (2014, 2014)
Title screen